The Effect of Public Sector Employment on Corruption - Gideon Nginyu, Giyoh (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
While the effect and determinants of corruption is well discussed in the literature, less attention has been given to how public sector employment affect corruption. The purpose of this paper is investigate the effect of public sector employment on corruption. Using data from 45 countries covering from 2002 through 2007, we employed Ordinary List Square (OLS) estimation technique to estimate the baseline model where we included both the linear and quadratic term of public sector employment to take of the non-linear relationship while adding a set of control variables. Our results suggest that public sector employment has a positive effect to control of corruption and beyond a particular threshold it turns to be a source of corruption. The results are robust even when we correct for endogeneity by using a static system-GMM technique of estimation. This means that governments should only employ a limited number of people which can permit her to render the basic functions of the state and make its economy more private sector oriented so as to scare away from corrupt practices.